THE DEVELOPMENT OF SOCIOLOGY AND ITS ROLE IN THE LIFE OF SOCIETY - Temirova Nilufar Erkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
Sociology is a science that studies, analyzes the relationships between a single whole society, its life, its problems and those who live in it, and can conclude by relying on empirical data through scientific methods. It is formed only through the society, sociology also develops if society matures. In this article, opinions and reflections are made on the development of sociology and its role in the life of society.